2020
DOI: 10.3390/jpm10040191
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Attitudes of Medical and Health Science Students in the United Arab Emirates toward Genomic Medicine and Pharmacogenomics: A Cross-Sectional Study

Abstract: Medical and health science students represent future health professionals, and their perceptions are essential to increasing awareness on genomic medicine and pharmacogenomics. Lack of education is one of the significant barriers that may affect health professional’s ability to interpret and communicate pharmacogenomics information and results to their clients. Our aim was to assess medical and health science students’ knowledge, attitudes and perception for a better genomic medicine and pharmacogenomics pract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 46 publications
5
31
0
Order By: Relevance
“…This study revealed that medical and pharmacy students at YU recognized the benefits of pharmacogenomics for therapy optimization. However, similar patterns of positive attitudes and insufficient exposure to pharmacogenomics information (such as reading articles or using online data resources) were reported among healthcare students of the University of Minnesota [23], the University of Zimbabwe [28], and universities in the United Arab Emirates [29]. Furthermore, this study revealed that 86% of future physicians and pharmacists supported providing pharmacogenetic testing in Jordan.…”
Section: Discussionsupporting
confidence: 66%
“…This study revealed that medical and pharmacy students at YU recognized the benefits of pharmacogenomics for therapy optimization. However, similar patterns of positive attitudes and insufficient exposure to pharmacogenomics information (such as reading articles or using online data resources) were reported among healthcare students of the University of Minnesota [23], the University of Zimbabwe [28], and universities in the United Arab Emirates [29]. Furthermore, this study revealed that 86% of future physicians and pharmacists supported providing pharmacogenetic testing in Jordan.…”
Section: Discussionsupporting
confidence: 66%
“…The main objective of pharmacogenomics is to assess the impact of an individuals' genetic makeup on drug efficacy and tolerance, and it is a vital factor in the new era of tailored medicine [18]. The field of pharmacogenomics is quite fresh in the Middle East.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the assessment of PGx and PM coverage in undergraduate education, recent studies also evaluated the perception and awareness of undergraduates on related concepts, with most undergraduates having a positive attitude towards PGx and PM [56][57][58][59]. These studies served as the groundwork for educational bodies on revising curriculum maps; and for the national and international community to determine the future direction of implementing PGx and PM into public education and clinical practice.…”
Section: Introductionmentioning
confidence: 99%